Serum netrin-1 in relation to gadolinium-enhanced magnetic resonance imaging in early multiple sclerosis. Issue 3 (August 2017) - Voortman, MM; Pekar, T; Bachmayer, D; Archelos, J-J; Stojakovic, T; Scharnagl, H; Ropele, S; Pichler, A; Enzinger, C; Fuchs, S; Fazekas, F; Seifert-Held, T; et al.
Background: Netrin-1, a secreted laminin-related protein, is known to regulate not only axonal guidance and neuronal cell migration, but also blood–brain barrier integrity and inflammation. Two preliminary studies reported altered serum netrin-1 levels in multiple sclerosis; however, associations with longitudinal clinical and magnetic resonance imaging activity have not been investigated. Objectives: We aimed to assess serum netrin-1 in multiple sclerosis and controls with respect to disease activity and its temporal dynamics. Methods: Serum netrin-1 was assessed by enzyme-linked immunosorbent assay in 79 patients with clinically isolated syndrome or multiple sclerosis, and 30 non-inflammatory neurological disease controls. In patients, serum samples were collected immediately prior to gadolinium-enhanced 3 T magnetic resonance imaging at two time points (initial contrast-enhancing gadolinium+ n  = 47, non-enhancing gadolinium– n  = 32; reference gadolinium– n  = 70; median time-lag 1.4, interquartile range 1.0–2.3 years). Results: Serum netrin-1 levels were similar in clinically isolated syndrome, multiple sclerosis and controls, and gadolinium+ and gadolinium– patients. Among gadolinium+ patients, serum netrin-1 was decreased in clinically active ( n  = 8) vs non-active patients ( n  = 39; p  = 0.041). Serum netrin-1 showed no temporal dynamics in multiple sclerosis and was unrelated to clinical data. Conclusions: Serum netrin-1 levels show no multiple sclerosis specific changes and are not sensitive for detection of subclinical disease activity. Netrin-1 changes during relapses may deserve further examination.